1993
DOI: 10.1111/j.1399-3054.1993.tb05504.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant metal content, growth responses and some photosynthetic measurements on field‐cultivated wheat growing on ore bodies enriched in Cu

Abstract: Some elemental levels, morphological and photosynthetic characteristics and cellular metabolites of wheat plants (Triticum aestivum L. cv. Vergina) growing in the field on an ore body (Cu concentration in the soil 3050 ug g−1) were compared to control plants growing in the same environment where the Cu concentration in the soil was 140 μg g1. The concentrations of Cu, K, Pb, Zn, Mg and Fe were higher in the ore plants but Ca was lower. Growth of the ore plants was inhibited, with decreased height (25%), weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
5

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 45 publications
(32 reference statements)
1
29
0
5
Order By: Relevance
“…These phenomena resulted in a decrease in the in vivo quantum yield of PSII activity. The decrease in the rate of total electron transport in stressed plants caused by excess Cu (Lanaras et al 1993) is likely to be related to the lower values of the assimilation rate (A) observed in the same Cu-stressed conditions reported herein. Productivity and stomatal conductance in the field-grown ore wheats decreased with a resultant reduction in transpiration and total water loss.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…These phenomena resulted in a decrease in the in vivo quantum yield of PSII activity. The decrease in the rate of total electron transport in stressed plants caused by excess Cu (Lanaras et al 1993) is likely to be related to the lower values of the assimilation rate (A) observed in the same Cu-stressed conditions reported herein. Productivity and stomatal conductance in the field-grown ore wheats decreased with a resultant reduction in transpiration and total water loss.…”
Section: Discussionmentioning
confidence: 51%
“…1994;Ouzounidou 1994). Lower values of CO 2 assimilation under Cu-stress were associated with a lower chlorophyll content (Table I) and parallel decreases in the concentrations of reducing carbohydrates (Lanaras et a!. 1993).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Entretanto, a presença em altas concentrações no solo afeta negativamente o crescimento e a produtividade das plantas (Sonmez et al, 2006), devido aos danos às membranas celulares por meio da peroxidação de lipídios (Bueno e Piqueras, 2002), ao comprometimento da atividade fotossintética (Lanaras et al, 1993) e aos processos de absorção e assimilação de nutrientes (Llorens et al, 2000;Devriese et al, 2001). Em solos agrícolas, um dos principais fatores relacionados ao aumento do teor de Cu em níveis fitotóxicos é a utilização intensiva de fungicidas cúpricos (Pietrzak e McPhail, 2004;Mirlean et al, 2007).…”
Section: Introductionunclassified